Some Properties of the Strong Primitivity of Nonnegative Tensors - Lihua You; Yafei Chen; Pingzhi Yuan (Journal of Applied Mathematics)
We show that an order m dimension 2 tensor is primitive if and only if its majorization matrix is primitive, and then we obtain the characterization of order m dimension 2 strongly primitive tensors and the bound of the strongly primitive degree. Furthermore, we study the properties of strongly primitive tensors with n≥3 and propose some problems for further research.